2003
DOI: 10.1002/jnr.10808
|View full text |Cite
|
Sign up to set email alerts
|

Mild carbon monoxide exposure and auditory function in the developing rat

Abstract: We have examined the influence of chronic mild exposure to carbon monoxide (CO) on cognitive (learning) and auditory function in the developing rat. We have demonstrated that the auditory pathway is compromised at exposures less than 50 ppm, whereas learning was not influenced at 100 ppm. Artificially reared rat pups were exposed to CO during the brain growth spurt and onset of myelination. Spatial learning was assessed using the Morris Water Maze and three tests of auditory function: (1) auditory brainstem co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 63 publications
(88 reference statements)
1
21
0
Order By: Relevance
“…For example, Huttenlocher and de Courten [25] found that the greatest increases in synaptogenesis in the occipital cortex occur between 2.5 and 8 postnatal months; however, this process is relatively slower in the frontal cortex where synapse formation does not reach its maximum density until after 15 postnatal months. Third, influences of myelin development on the morphology of waveforms have been demonstrated in animal studies [26], showing that brain responses can be impaired if the brain is exposed to carbon monoxide during the developmental stage of myelination [27]. Moreover, the number of neurons involved in the sensory processes may vary at different ages.…”
Section: Morphological Changes Of Erp Componentsmentioning
confidence: 99%
“…For example, Huttenlocher and de Courten [25] found that the greatest increases in synaptogenesis in the occipital cortex occur between 2.5 and 8 postnatal months; however, this process is relatively slower in the frontal cortex where synapse formation does not reach its maximum density until after 15 postnatal months. Third, influences of myelin development on the morphology of waveforms have been demonstrated in animal studies [26], showing that brain responses can be impaired if the brain is exposed to carbon monoxide during the developmental stage of myelination [27]. Moreover, the number of neurons involved in the sensory processes may vary at different ages.…”
Section: Morphological Changes Of Erp Componentsmentioning
confidence: 99%
“…Chronic mild postnatal CO exposure has also been shown to impair the developing auditory system (Lopez, 2003; Stockard-Sullivan, 2003; Webber, 2003). Expression of c-Fos, an indicator of neuronal activation following sound stimulation, was found to be significantly decreased in the central nucleus of the inferior colliculus in 27 day old rats following chronic postnatal exposure to between 12 and 50 ppm CO beginning on the eighth day of life (Webber, 2003).…”
Section: Low Concentration Co Exposure and Subclinical Neurotoxicitymentioning
confidence: 99%
“…Expression of c-Fos, an indicator of neuronal activation following sound stimulation, was found to be significantly decreased in the central nucleus of the inferior colliculus in 27 day old rats following chronic postnatal exposure to between 12 and 50 ppm CO beginning on the eighth day of life (Webber, 2003). In addition, chronic postnatal exposure to 50 ppm CO beginning at the onset of myelination was shown to attenuate the amplitude of conduction of the eighth cranial nerve in newborn rats (Stockard-Sullivan, 2003). Interestingly, exposure to 100 ppm CO, yielding a mean COHb level of 10.2%, had no effect on eighth cranial nerve conduction suggesting that lower levels of CO exposure were responsible for the pathologic effects (Stockard-Sullivan, 2003).…”
Section: Low Concentration Co Exposure and Subclinical Neurotoxicitymentioning
confidence: 99%
See 2 more Smart Citations